'I've got Parkinson's and that makes a difference': Understanding health and leisure through a Parkinson's disease diagnosis. Issue 1 (2nd January 2019) - Stilwell, Christie L.; Hutchinson, Susan L.; Meisner, Brad A.
Abstract : Parkinson's disease (PD) is a degenerative neurological disorder that impacts all aspects of life, including leisure. Although there are numerous investigations of the constraints to leisure participation experienced by adults living with acquired disabilities and illnesses, to date there are limited studies on the experiences of living with PD. This qualitative study, involving in-person or telephone interviews with five persons recently diagnosed with PD, sought to explore: (a) relationships among PD, leisure participation, and physical, mental, and social health; and (b) the ways that leisure is a component of coping with and self-managing PD. Three overarching themes were constructed using thematic analysis: (a) leisure participation prior to diagnosis; (b) the impact of emerging PD symptoms on leisure participation; and (c) the role of leisure in living well with PD. Results are discussed in relation to the role of various forms of leisure in reducing social isolation and self-managing PD.